Improving enzyme production by solid-state cultivation in packed-bed bioreactors by changing bed porosity and airflow distribution - Perez, Caroline Lopes [UNESP]; Casciatori, Fernanda Perpétua; Thoméo, João Cláudio [UNESP] (Springer Nature, 2021)
Enzymes production by solid-state cultivation in packed-bed bioreactor needs to be improved by mathematical modeling and also by experimentation. In this work, a mixture of sugarcane bagasse and wheat bran was used for the growth of the fungus Myceliophthora thermophila I-1D3b, able to secrete endoglucanase and xylanase, enzymes of interest in the second-generation ethanol production. Bench and pilot-scale bioreactors were used for the experiments, while critical parameters as bed porosity and airflow distribution were evaluated. Results showed enzymes with higher activities for the most porous medium, even though the less substrate amount to be cultivated. For the pilot-scale bioreactor, only the most porous medium was evaluated using different airflow distribution techniques. Using an inner tube for air supply resulted in more homogeneous enzyme production, with higher activities. The results here presented will be helpful for the scale-up of this class of bioreactor into industrial apparatuses.
Keywords: Cellulase; Fixed bioreactor; Packing density; Scale-up; Solid-state fermentation